PELATIHAN PENINGKATAN PEMAHAMAN MASYARAKAT TERHADAP ASPEK HUKUM TINDAKAN BULLYING/PERUNDUNGAN - Husna, Lenny; Nurma Dhona Handayani; Ukas, Ukas; Arman, Zuhdi (PUAN INDONESIA, 2024)
Bullying is an action that is not new and occurs in society, especially among teenagers. In the past, we often used the term "April Fool's" where people were considered allowed to lie or tell jokes to other people without being considered guilty on a certain day. This day is marked by cheating and other pranks on friends with the aim of humiliating gullible people. This action under the guise of a "joke" is considered normal, but in many cases it has extraordinary impacts. In many cases, these actions cause damage to the victim's mental condition and even have an impact on the victim's psychology, some even commit suicide as a result of their actions under the guise of a "joke". Bullying is currently done by being oppressed, pressured, and so on. Bullying or harassment can be through words or through actions aimed at making the opponent's mental state worse and depressed. Another goal is to control someone through insulting, high-pitched words, threats, or violent actions. This is very likely to happen in various areas of society, both in the home, community and school environment, this is due to a lack of public understanding regarding bullying and its legal aspects. Therefore, coaching is related to the legal aspects of bullying and the ethics of using language in communication. Whether directly or through the media, this is very important and must always be done to create a superior social life.